Iron deficiency following bariatric surgery: a retrospective cohort study - Zachary Gowanlock; Anastasiya Lezhanska; Maeve Conroy; Mark Crowther; Maria Tiboni; Lawrence Mbuagbaw; Deborah Siegal (2020)
Abstract Iron deficiency is a common consequence of bariatric surgery and frequently leads to anemia. Our study reports the incidence and predictors of iron deficiency, iron deficiency anemia (IDA), and IV iron use after bariatric surgery. We conducted a retrospective study of all adult patients who underwent bariatric surgery from January to December 2012 at the regional bariatric surgery center in Hamilton, Ontario, Canada, and were followed for at least 6 months. Time-to-event data were presented as Kaplan-Meier curves. Cox regression analysis was used to identify outcome predictors. A total of 388 patients met the inclusion criteria. Iron deficiency, IDA, and the use of IV iron were reported in 43%, 16%, and 6% of patients, respectively, with a mean follow-up of 31 months. The cumulative incidence of iron deficiency and IDA increased with longer follow-up, and there was a significant increase in IV iron use starting 3 years after surgery. Malabsorptive procedures (hazard ratio [HR], 1.92; 95% confidence interval [CI], 1.20-3.06; P = .006) and low baseline ferritin (HR, 0.96; 95% CI, 0.95-0.97; P < .001) were associated with an increased risk of iron deficiency. Young age (HR, 0.90; 95% CI, 0.82-0.99; P = .028), baseline anemia (HR, 19.6; 95% CI, 7.85-48.9; P < .001), and low baseline ferritin (HR, 0.96; 95% CI, 0.95-0.98; P < .001) were associated with an increased risk of IDA. Our results suggest that IDA is a delayed consequence of bariatric surgery and that preoperative assessment of patient risk may be possible.